INDUCTIVE APPROACH IMPLEMENTATION TO IMPROVE THE MATHEMATICHAL REASONING, PROBLEM-SOLVING, AND SELF-CONCEPT OF JUNIOR HIGH SCHOOL STUDENTS IN KARAWANG DISTRICT - Yuli Mulyasari (Universitas Suryakancana, 2018)
Inductive Approach is an alternative that is offered to overcome the problem of low mathematical reasoning ability, problem-solving, and self-concept of students. The population in this study is all students of state SMP in Karawang district. The selected sample is for the students of class VIII SMP Negeri 2 Pangkalan, Karawang district in the academic year 2017-2018. Sampling was done by sampling technique, in random sampling was taken 1 experiment class and 1 control class. The result of the research shows improvement of reasoning ability and mathematical problem solving of students who gain learning with the inductive approach is better than students who get regular learning. The self-concept of students acquiring learning with an inductive approach is smaller or equal to that of students who acquire regular learning. The association between reasoning ability and mathematical problem solving is in the moderate category. The association between reasoning ability and student self-concept is in a low category. The association between problem-solving ability and student self-concept is in a low category. The description of the learning process with the Inductive Approach is already in line with the syntax of learning with the Inductive Approach. As for the students' difficulties in working on problems of reasoning and problem solving, among others, the difficulty of identifying the interrelationships between concepts, the difficulty of identifying strategies that can be taken, carrying out calculations, and careless in re-examining the solutions obtained. Keywords: inductive approach, mathematical reasoning, mathematical problem-solving, self-concept.